Scientific production associated with the fields of action formed administrator at the National University Pedro Ruiz Gallo - Echeverría Jara, José Foción (2016)
In the professional career of Administration, the specialist teachers have limited production Scientific perspective of little relation with the fields of action of the professional race; Students are poorly involved in research, a situation that does not allow the reinforcement of scientific knowledge in their training. For these aspects, this study is important, because it will serve to assess the production Scientific research of the specialist teachers and link them with the fields of action of the administrator that is formed at the National University Pedro Ruiz Gallo. The problem was defined as follows: Is there an association between scientific production and Action of the administrator that form in the National University Pedro Ruiz Gallo?, As hypothesis was considered "The scientific production of the professors specialists of the professional career of administration is disconnected with the fields of action of the administrator in formation, making of the unscientific formative process Already systemic".